Comments on Main Factors Affecting Electricity Price Risk in Turkish Electricity Market - Gözen, Mustafa (Muş Alparslan Üniversitesi, 2020)
Türkiye elektrik piyasasında 2001 yılında başlayan serbestleşme sürecinin getirdiği en önemli değişikliklerden biri, elektrik fiyat riskinin ortaya çıkmasıdır. 2003 yılından itibaren, serbest tüketiciler tedarikçileri ile ikili anlaşma kapsamında uzlaştıkları fiyattan elektrik satın alabilmektedir. Bunun yanında, serbest olmayan tüketiciler ile kırılgan tüketiciler için Energy Piyasası Düzenleme Kurumu (EPDK) tarafından belirlenen fiyatlar dışında kalan elektrik fiyatları, 2006 yılı Mayıs ayından itibaren serbest piyasa koşullarında oluşmaktadır. Bu itibarla, bu makalenin amacı; Türkiye elektrik piyasasında fiyat riskine neden olan ana faktörlerin incelenmesidir. Bu makalede altı başlık altında toplanan faktörler ayrıntılı olarak incelenmiştir.

One of the most important changes brought about by the liberalization process in Turkish electricity market that started in 2001, is the emergence of electricity price risk. Since 2003, eligible consumers have been able to purchase electricity at a price agreed upon under a bilateral agreement with their suppliers. In addition to this, electricity prices, which are outside the prices determined by Energy Market Regulatory Authority (EPDK) for non-eligible consumers and vulnerable consumers, have been formed under free market conditions since May 2006. In this respect, the purpose of this article is to examine the main factors that lead to price risk in Turkish electricity market. The factors classified under six headings in the article were examined in detail.
Türkiye Elektrik Piyasasında Elektrik Fiyat Riskini Etkileyen Temel Faktörler Hakkında Yorumlar
anemon
Keywords: Elektrik piyasası; Elektrik fiyat riski; Türkiye elektrik piyasası; Risk yönetimi; Gün öncesi piyasası; Electricity market; Electricity price risk; Turkish electricity market; Risk management; Day ahead market